2021
DOI: 10.1063/5.0025492
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial horizontal axis hydrokinetic turbine system: Numerical modeling and performance optimization

Abstract: Hydrokinetic turbines extract energy from free-flowing water, such as river streams and marine currents. For river applications, the typical deployment location is highly space-constrained due to both the nature of the river (i.e., its natural width and depth) and the other usages of the river. Therefore, a modified design of a conversion device is desired to accommodate these space limitations. The objective of this work is to derive optimum design criteria for a coaxial horizontal axis hydrokinetic turbine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These two variables are further explored in a parametric analysis considering the extended range 𝑧 = 1 − 5 and 𝜆 des = 1−12. In addition, two high 𝐶 𝐿 ∕𝐶 𝐷 hydrofoils commonly used in hydrokinetic turbines are examined, SG-6043 and EPPLER-E836, with (𝐶 𝐿 ∕𝐶 𝐷 ) max ≈ 40 − 170 and (𝐶 𝐿 ∕𝐶 𝐷 ) max ≈ 30 − 60 at 𝑅𝑒 = 5 × 10 4 − 10 6 , respectively (see, e.g., [14,41,[65][66][67]).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two variables are further explored in a parametric analysis considering the extended range 𝑧 = 1 − 5 and 𝜆 des = 1−12. In addition, two high 𝐶 𝐿 ∕𝐶 𝐷 hydrofoils commonly used in hydrokinetic turbines are examined, SG-6043 and EPPLER-E836, with (𝐶 𝐿 ∕𝐶 𝐷 ) max ≈ 40 − 170 and (𝐶 𝐿 ∕𝐶 𝐷 ) max ≈ 30 − 60 at 𝑅𝑒 = 5 × 10 4 − 10 6 , respectively (see, e.g., [14,41,[65][66][67]).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…They showed that optimization of the hydrofoil cross-section (compared to a NACA 4415 hydrofoil) can improve the efficiency by 26% for speeds between 0.5-2 m s −1 and by 50% for speeds between 2-3 m s −1 (𝐶 𝑃 = 0.3-0.45). Abutunis et al (2021) [14] examined experimentally and numerically the design of a coaxial horizontal-axis hydrokinetic turbine system. They found that a three-turbine axial system placed in series can increase the power output by 47% compared to a single-turbine system under optimal-solidity design conditions.…”
Section: Introductionmentioning
confidence: 99%